Impacto da Pandemia de Covid-19 sobre os retornos das ações da carteira IBRX100 da B3 à luz das Finanças Comportamentais e Eficiência de Mercado - Wohlemberg, Tiago Ramos (2022)
Understanding the impact of the covid-19 pandemic on stock markets in terms of its potential to influence investor behavior so that abnormal returns arise in asset trading is important to identify how a global scale event, which generates a high level of uncertainty and a large volume of new information, affects asset prices. With this in mind, the objective of this study was to analyze the impact of the advent of the covid-19 pandemic on investor behavior and market efficiency on the Brazilian Stock Exchange, especially on the IBrX100 asset portfolio. To analyze the occurrence of abnormal returns and whether semi-strong market efficiency was verified during and after the initial impact of the pandemic, the event study technique proposed by MacKinlay (1997) and Campbell, Lo & MacKinlay (1997) was applied in which three trading windows of the assets of the IBrX100 portfolio were listed (estimation window - before the announcement; event window - around the announcement; and post-event window). Average abnormal returns and average accumulated returns had their means tested by Student's t test and Wilcoxon's rank-signal test, and it was found that they were different from 0 in all time windows, which confirms their abnormality. These same tests were conducted to verify whether there was a statistical difference between the average abnormal returns and average accumulated returns of the different time windows. The means were statistically different in the three periods, going from slightly positive during the estimation window to negative around the announcement of the pandemic and then to noticeably positive during the post-event period, which goes against the idea of an efficient market. To bring explanations about the behavior of investors when they are influenced by news about the economic impact of the new coronavirus, Bardin's (2011) thematic content analysis technique was used. From this, it was possible to understand that the fear and uncertainty about the global economy linked to the covid-19 pandemic, emphasized by the media vehicles, led IBrX100 investors to act in a non-rational way when trading their assets, thus presenting herd behavior, as this coincided with a period of significant declines in asset prices. When comparing these results with other studies, it was found that the performance of the IBrX100 index was affected in a similar way to the indexes of markets around the world in terms of the presence of abnormal returns, market inefficiency and herd behavior of investors. The present study contributes to the Efficient Markets Hypothesis by demonstrating how an event of high economic impact can compromise the semi-strong efficiency of a representative market index. It also contributes to Behavioral Finance by showing that IBrX100 investors were driven by the biases of economic uncertainty and fear constantly disseminated by the media, which caused large losses to the portfolio during the period surrounding the announcement of the pandemic.